Design of a Profile Website and New Student Admission System (PPDB) to Improve School Competitiveness at Mts Al-Washliyah Sei Mencirim - Nabila Dwi Sekar Arum; Hanna Willa Dhany; Hendry (Bahasa Indonesia, 2026)
The development of information technology has encouraged institution education to adopt digital systems to improve quality services and dissemination of information to community. MTs Al- Washliyah Sei Mencirim Still facing obstacles in delivering school information and the Admissions process Participant New Student Admissions (PPDB) which is mostly carried out conventionally, so it is less effective and efficient in data management and service to candidate participant This research aims to design and build a School Profile Website and Admissions System Participant Web- based New Student Admissions (PPDB) for increase effectiveness information services and registration process participant new students. The system development method used is Waterfall which consists of from stages requirements analysis, system design, implementation, testing, and maintenance. The system was developed using the PHP programming language, MySQL database, and the Bootstrap framework to support the display. responsive interface. System testing is carried out using the Black Box Testing method to ensure that all The system functions according to user needs. The research results show that that the system built is able to provide school information more quickly and easily accessible to the public, simplifying the registration process participant new students online, as well as assisting administrators in managing registration data in a structured and integrated manner. All system features successful running well based on the results of the tests conducted. Thus, the implementation of the school profile website and web- based PPDB system can be increase quality service education and support the improvement Power competition of MTs Al- Washliyah Sei Mencirim in the digital era.